Renal angiomyolipomas in tuberous sclerosis—rare but potentially life-threatening lesions. (14th December 2012) - Azim, Adnan; Rajkumar, Govindaraj
Abstract : We discuss an 18-year-old girl, diagnosed with tuberous sclerosis complex and known to have renal angiomyolipomas (AMLs) but having no regular urological follow-up, who presented with left-sided abdominal pain and haematuria on urine dipstick testing at the out-of-hours General Practitioner (GP) service. She was diagnosed as having urinary tract infection/pyelonephritis and discharged with simple analgesia and antibiotics. Subsequent imaging of her renal tract demonstrated multiple large AMLs with evidence of recent bleeding, which required arterial embolisation.